استخدام مواقع التواصل الاجتماعي ( الفيسبوك) وحالة الاغتراب الثقافي لدى الطلبة الجامعيين - إيمان نجاح بن أحمد; إلهام قمري; د/عبدالقادر علال (جامعة عمار ثليجي الاغواط, 2023)
ملخص: تهدف هذه الدراسة إلى التعرف على إستخدام مواقع التواصل الإجتماعي"الفيسبوك" و حالة الإغتراب الثقافي لدى الطلبة الجامعيين الجزائريين، فالإغتراب الثقافي من بين أهم المواضيع التي نالت إهتمام الباحثين خاصة مع التطور التكنولوجي و الغزو الفكري الذي نعيشه. و انطلاقا من عملية البحث من خلال دراستنا على أهم مظاهر الإغتراب الثقافي الناتجة على إستخدام موقع "الفيسبوك" و عادات إستخدامه و المضامين التي يتعرض لها الطالب من خلال هذا الموقع مع تقديم إقتراحات رئيسية لحماية الطالب من ظاهرة الإغتراب الثقافي،وصولا إلى أهم النتائج التي تناولتها هذه الدراسة ، والتي أكدت في مجملها على وجود ظاهرة الإغتراب الثقافي في موقع التواصل الإجتماعي "الفيسبوك" من خلال عدة مظاهر، تتعلق بأهم مكونات و خصوصيات الهوية الثقافية لدى أفراد المجتمع بصفة عامة، و الطلبة الجامعيين الجزائريين خاصة. Abstract : This study aims to identify the use of social networking sites "Facebook" and the state of cultural alienation among Algerian university students, cultural alienation is one of the most important topics that have received the attention of researchers, especially with the technological development and intellectual invasion that we are living. And starting from the research process through our study on the most important manifestations of cultural alienation resulting from the use of the site "Facebook" and the habits of using it and the contents to which the student is exposed through this site, with the provision of key suggestions to protect the student from the phenomenon of cultural alienation, up to the most important results addressed by this study, which in its entirety confirmed the existence of the phenomenon of cultural alienation in the social networking site "Facebook" through several manifestations, related to the most important components and peculiarities of cultural identity among members of society in general, and Algerian university students in particular
دراسة ميدانية على عينة من طلبة قسم الإعلام والاتصال بجامعة الأغواط